Influence of persistently recurring pterygium on the optical interface of the cornea - E.N. Bilalov; A.F. Yusupov; A.E. Nozimov; O.I. Oripov (Ukrainian Society of Ophthalmologists, 2020)
Background: Pterigiym is a proliferative, degenerative and inflammatory disease developing due to pathological hyperplasia, vascularization of the epithelium and migration of abnormal limbal stem cells to the central cornea, and accompanied by profound changes in the structure of underlying tissue. Purpose: To assess the influence of persistently recurring pterygium on the optical interface of the cornea using refractometry and corneal topography. Material and Methods: Sixty patients (67 eyes) with persistently recurring pterygium were included in this study. Patients were divided in four groups based on the number of recurrences. They underwent visual acuity assessment, refractometry and computerized corneal topography to assess the optical interface of the cornea. Results: We found significant differences in visual acuity, refractive errors and corneal topography indices among patients with persistently recurring pterygium with various numbers of recurrences. Our case follow-up demonstrated that permanent changes in the optical interface of the cornea developed with an increase in recurrences and persistence of growth of wing-shaped conjunctiva onto the cornea; these changes manifested as residual corneal astigmatism. Conclusion: An increase in pterygium recurrences results in permanent impairments of the optic interface of the cornea; this requires developing advanced surgical techniques capable of preventing recurrence of pterygium.